Efficacy of herbal essential oils as insecticides against the housefly, Musca domestica L. - Sinthusiri, Jirisuda; Soonwera, Mayura (My University, 2013)
The insecticidal effects of 20 essential oils derived from herbs, were tested against the housefly species Musca domestica L. using a susceptibility test. Each was applied in ethyl alcohol at concentrations of 1, 5 and 10% (v/v). Ten percent concentrations of Cymbopogon citratus (lemongrass), Mentha piperita (peppermint) and Lavandula angustifolia (lavender) oils were the most effective, showing 100% knockdown at 30 and 60 minutes. The KT50 values for C. citratus, M. piperita and L. angustifolia were 5.14, 5.36 and 8.23 minutes, respectively. These essential oils caused 100% mortality among houseflies 24 hours after exposure. The LC50 values for C. citratus, M. piperita and L. angustifolia were 2.22, 2.62 and 3.26 minutes, respectively. This study reveals lemongrass, peppermint and lavender essential oils have the potential to control housefly populations and should be further studied for field applications.
Keywords: Essential oil; Housefly; Insecticidal activity; Musca domestica L.